China syndrome - "Pant ,Harsh V" (New Delhi, 2010)
As the balance of power shifts from the West to the East, the relationship between the two regional giants, China and India, gains significance. Their relationship will determine to a great extent the new political architecture that takes shape in Asia and the world at large. Nor are the two powers unaware of this. As a Chinese premier meeting the Indian prime minister is reported to have said, 'When we shake hands, the whole world will be watching.' The China Syndrome seeks to decipher the complex, multi-layered relationship between the two countries, and the strategy or lack of it in India's China policy. Given the emerging scenario, it is a subject of considerable interest.
Keywords: China-India-Foreign relations